Geochemical evaluation pollution for some heavy metals in basra soil - Al-Bedhany, Abbas (University of Thi-Qar Journal of Science, 2015)
The present study included determine concentrations of certain heavy metals (lead, cadmium, cobalt, copper,zinc, nickel, iron and manganese) of surface soils in selected areas of North, South and west of Basra governorate consisted of four seasons from autumn 2013 to summer 2014 by using Flame atomic absorption spectrum. The seasonal variation of these elements range from lowest value (1.80µg/g) for cadmium in winter and the highest value (13033.18µg/g) for iron in the summer. Total organic carbon TOC% and grain size analysis where also determined and there is not correlation between them, these factors suggesting that working in high concentrations of certain heavy elements in Basra than in natural soils is pollution from human activities. Geochemical index (Igeo) where also determined that average concentration ranged from less value (3.32) for cadmium and the highest value (18.81) for iron. While the Enrichment factor (EF) range from less value (0.0005) for manganese and highest value (0.414) for cadmium. Finally Contamination factor (CF) range from less value (0.46) for zinc and the highest value (223.21) for  iron. Basra contaminated soil with heavy elements increase is attributable to human and industrial activities such as increased transportation vehicles and burning gasoline and from other facilities such as hospitals, power plants and oil companies, as well as the use of phosphate fertilizers in agricultural areas, as well as some industrial parks to increase concentrations of some heavy metals in the soil.